BRIDGING THE GAP: A COLLABORATIVE RESEARCH AND EDUCATION PROGRAM FOR PHARMACISTS AND PHYSICIANS - Singh, Anika; Dubois, Michael; Garcia, Elena (Ayden Journal of Drug and Pharmaceutical Research, 2024)
Evidence-based medicine (EBM) is crucial for enhancing patient care, and understanding the methods behind EBM is essential for healthcare providers to engage in research and contribute to medical advancements. However, there is a lack of standardized research training for medical residents, with programs differing in their approach to research education. This study aims to investigate the variability in research training curricula for medical residents and assess the effectiveness of different approaches. A standardized approach to research training may help bridge the gap between EBM and clinical practice, ultimately leading to improved patient care.